Effects of structure height and temperature to power generation of a 4.86 kWp solar land - Simala, Suthep; Roynarin, Wirachai (Center of Biomass & Renewable Energy (CBIORE), 2025)
Efficient heat transfer significantly improves both the efficacy of photovoltaic (PV) systems and the longevity of PV panels. Lower temperatures facilitate improved power generation and minimize heat-related damage. Conduction, convection, and radiation are the primary heat transfer mechanisms that are involved in this process. This study investigated the effects of PV panel structure heights—specifically 1 meter, 1.5 meters, and 2 meters—on the temperature differences between the top and bottom of the panels, as well as their corresponding power generation, while accounting for the heat transfer that occurred. The PV system comprised nine 540-watt monocrystalline PV panels arranged at these three heights in Khlong Si, Khlong Luang, and Pathum Thani. Data on temperature, power output, and other meteorological variables were collected at 5-minute intervals from 6:00 AM to 6:00 PM over a two-month period from March to April 2024. To evaluate the impact of panel height on performance, all collected data were analyzed. The actual power outputs were compared with simulations conducted using PVsyst. Additionally, the costs associated with each panel height were assessed to identify the optimal height that would achieve both high power output and low costs. The findings revealed that increasing the panel height contributed to a reduction in temperature buildup within the panels and enhanced power output, with increases of 8.87% and 9.45% observed at heights of 1.5 meters and 2 meters, respectively. However, this increase in height also resulted in cost escalations of 24.51% and 48.04%, respectively. Consequently, it was determined that the optimal height was 1.5 meters, as it provided an effective balance between maximizing power output and minimizing costs. Furthermore, the results from the PVsyst simulations indicated significant discrepancies, with measured values approximately 20% lower than expected.